One-Step Enrichment of Intact Glycopeptides From Glycoengineered Chinese Hamster Ovary Cells - Yang, Ganglong; Höti, Naseruddin; Chen, Shao-Yung; Zhou, Yangying; Wang, Qiong; Betenbaugh, Michael; Zhang, Hui (Frontiers in Chemistry, 2020)
Recently glycoproteomic analysis of intact glycopeptides has emerged as an effective approach to decipher the glycan modifications of glycoproteins at the site-specific level. A rapid method to enrich intact glycopeptides is essential for the analysis of glycoproteins especially for biopharmaceutical proteins. In this study, we established a one-step method for the rapid capture of intact glycopeptides for the analysis by mass spectrometry. Compared to the conventional sequential enrichment method, the one-step intact glycopeptide enrichment method reduced sample preparation time and improved the detection of intact glycopeptides with long sequences or nonpolar amino acids. When we applied this method to the glycoproteomic analysis of glycoengineered CHO-K1 cells with α1,6-fucosyltransferase (FUT8) knockout, the results showed that the knockout of FUT8 altered the overall glycosylation profile of CHO-K1 cells with the elimination of core fucosylation together with increases in high-mannose and sialylated N-glycans. Interestingly, the knockout of the FUT8 also appeared to regulate the expression of glycoproteins involved in several functions and pathways in CHO-K1 cells, such as the down-regulation of an intracellular lectin LMAN2 protein indicating cellular adaptation to the alterations in FUT8 knockout cells. These findings indicate that site-specific characterization of glycoproteins from glycoengineered CHO-K1 cells can be achieved rapidly, which provide insights for bio-analysts and biotechnologists to better tailor therapeutic drugs.